(untitled) (Ágora Journal, 2023)
As of the analyses of inventories, testaments, notaries’ books, passports e periodicals published in the Province of Bahia and in another parts of the Brazilian Empire in the nineteenth century, this article seeks to comprehend the trajectory of freed crioula Leonarda Maria da Conceição and her family network, as well as her relationships established with the Sociedade Libertadora Sete de Setembro, an important baiana emancipacionist association in the 1870s. I propose to respond how the Sociedade Libertadora Sete de Setembro crossed the path of this black family. Furthermore, this article has also the objective of understanding what extent this black family’s journey in particular enlightens others struggles for freedom and in which way the black motherhood was used by emancipacionists and what it might represent.